URGENSI PEMBENTUKAN PERATURAN MENGENAI SKEMA PONZI DI INDONESIA - Sari, Madelin Ezra; Rinwigati, Patricia (Universitas Ekasakti, 2023)
The emergence of the phenomenon of illegal investment which is often associated with Ponzi schemes is an issue that deserves to be studied because it is very close to our surrounding life. The Ponzi scheme that is developing in Indonesia is actually not the same as investment fraud, but is the method used to carry out this crime. In its development, ponzi schemes have evolved into various forms of investment products. However, the ongoing developments in Indonesia have not been followed by the strengthening of regulations governing ponzi schemes. Therefore, there are obstacles in handling cases that use ponzi schemes as well as in ineffective prosecutions due to sectoral regulations used to prosecute ponzi scheme users.